Karakteristik dan Aktivitas Antioksidan Tepung Kulit Buah Naga (Hylocerus polyrhizus) pada Brownies Pukis Kulit Buah Naga (Bruga) - Lestari, Putri Kurnia; Nazihah, Fathimah Qonita; Nadhilah, Aulia Shafra; Safitri, Qorina Amalia; Isnawati, Isnawati (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
Dragon fruit is a fruit that contains many benefits inside it. One part of the dragon fruit that has high nutritional value is the skin. The skin can be processed into products made into flour which can be used as an ingredient in cakes. The utilization of this dragon fruit skin to cakes can also add nutritional benefits to cakes itself. Dragon fruit skin flour itself has a rich content of antioxidants. These antioxidants have the benefit of protecting the body from various kinds of disease and can protect the body against the effects of free radicals. Apart from that, the utilization of this dragon fruit skin can be used to reduce dragon fruit waste which often pollutes the surrounding environment. This dragon fruit waste is still minimally utilized in the wider community so that accumulation often occurs. Therefore, holding this research can add efficacy and nutritional value to cakes and reduce the amount of dragon fruit peel waste in the surrounding environment to create a clean and eco-friendly environment. The purpose of this study is to analyze the characteristics and also the antioxidant activity contained in dragon fruit peel flour which would be made in the form of pukis brownies. These pukis brownies were divided into 3 concentrations, contain with 100% wheat flour, 50% dragon fruit peel flour, and 100% dragon fruit peel flour by analyzing the starch content and the influence of the quality of the pukis brownies in terms of shape, color, taste, smell and texture.